Salmonella Typhimurium Infection Along the Porcine Gastrointestinal Tract and Associated Lymphoid Tissues. Issue 5 (September 2019) - Bellido-Carreras, Natividad; Argüello, Héctor; Zaldívar-López, Sara; Jiménez-Marín, Ángeles; Martins, Rodrigo P.; Arce, Cristina; Morera, Luis; Carvajal, Ana; Garrido, Juan J.
Salmonella is a major foodborne pathogen and pork is one of the main sources of human salmonellosis. Understanding the pathogenesis and progression of the infection within the host is of interest to establish potential approaches to control the disease in pigs. The present study evaluates factors such as intestinal colonization, fecal shedding, and pathogen persistence by 2 studies using experimental challenge with Salmonella Typhimurium in weaned pigs and euthanasia at different time points (1, 2, and 6 and 2, 14, and 30 days postinfection [dpi], respectively). Histopathology of intestine at early time points (1 dpi and 2 dpi) showed severe damage to the epithelium together with an increase in polymorphonuclear cells and macrophages ( P < .001), particularly in jejunum and ileum. Large quantities of Salmonella were detected within the contents of the ileum, cecum, and colon in early infection. Salmonella could also be observed in the medulla of tonsils and mesenteric lymph nodes. From 6 dpi onward, signs of recovery were observed, with progressive restoration of the epithelium, reduction of the inflammatory infiltrate, and elimination of Salmonella from the mucosa. Concentration of Salmonella in feces and ileum content decreased, but shedding did not cease even at 4 weeks after infection. Persistence of the bacteria in mesenteric lymph nodes was identified within the connective tissue at 14 and 30 dpi. Our results demonstrate a recovery of the disease after an initial acute phase but also show persistence within the lumen and surrounding lymphoid tissue. These findings are relevant to developing effective control strategies.